Slow acoustic surface modes through the use of hidden geometry - S. R. Shelley (Nature Portfolio, 2021)
Abstract The acoustic surface modes supported by a partly covered periodic meander groove structure formed in an assumed perfectly rigid plate are investigated. This allows one to create a slower acoustic surface wave than can be achieved with the same uncovered meander structure. By changing the size of the uncovered section the phase and group speeds can be tuned. When the uncovered section of the meander structure is centred along the grooves then the distance along the grooves between neighbouring holes is the same on both sides of the structure so no band gap is observed at the first Brillouin zone boundary due to glide symmetry. This then gives quite linear dispersion. As the uncovered section’s position is moved away from the centre of the meander structure a band gap opens at the Brillouin zone boundary.